2008
DOI: 10.1681/asn.2007091040
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of BMP7 in the Regenerative Response to Ischemia

Abstract: Kidneys damaged by ischemia have the potential to regenerate through a mechanism involving intrarenal induction of protective factors, including bone morphogenetic protein-7 (BMP7). Epigenetic changes, such as alterations in histone modifications, have also been shown to play a role in various pathologic conditions, but their involvement in ischemic injury and regeneration remains unknown. This study investigated whether changes in histone acetylation, regulated by histone acetyltransferase and histone deacety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(85 citation statements)
references
References 43 publications
2
83
0
Order By: Relevance
“…It has been suggested that BMP-7 suppresses fibrosis by inhibiting TGF-β1 synthesis (36) and by controlling TGF-β signaling via blocking the nuclear translocation of phosphorylated Smad2/3 (37). In fact, the association between BMP-7 and histone acetylation has already been shown (22). Marumo, et al reported that marked induction of BMP-7 and the increase of strongly positive cells for acetylated histone were observed simultaneously in the proximal tubular cells during the recovery phase following renal ischemic reperfusion in mice (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that BMP-7 suppresses fibrosis by inhibiting TGF-β1 synthesis (36) and by controlling TGF-β signaling via blocking the nuclear translocation of phosphorylated Smad2/3 (37). In fact, the association between BMP-7 and histone acetylation has already been shown (22). Marumo, et al reported that marked induction of BMP-7 and the increase of strongly positive cells for acetylated histone were observed simultaneously in the proximal tubular cells during the recovery phase following renal ischemic reperfusion in mice (22).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports indicate that the expression of fibrosis inhibitory factors can be increased by promoting histone acetylation (21,22). As the effects of inhibitory factors for fibrosis, Yu et al reported that bone morphogenetic protein 7 (BMP-7) and hepatocyte growth factor (HGF) ameliorated high-glucose-induced epithelial-to-mesenchymal transition (EMT) of peritoneal mesothelial cells (23).…”
mentioning
confidence: 99%
“…The cDNA product was diluted to a volume of 200 l, and 5-l aliquots were used as templates for amplification using the SYBR Green PCR amplification reagent (Applied Biosystems) and gene-specific primers for BMP-7 (forward 5=-CGCTC-CAAGACGCCAAA-3= and reverse 5=-CCTCTGGTCACTGCT-GCTGTT-3=). Specific primers for BMP-7 were designed according to a previous report (13) and were checked to determine whether they showed a single peak in the dissociation curve. Kidney SP cells obtained just after FACS sorting were resuspended in RNAprotect Cell Reagent (Qiagen).…”
Section: Animalsmentioning
confidence: 99%
“…Despite the potential role of HDAC in molecular responses to kidney injury, changes in the expression of HDAC and histone acetylation in the kidney have not been characterized. In this regard, we recently reported that HDAC5 downregulation, which leads to histone acetylation in renal tubular cells, contributes to the regenerative response to ischemia (21).…”
mentioning
confidence: 99%